THE TELEOLOGICAL PROBLEM OF ECONOMIC RATIONALITY: MAXIMIZATION, BOUNDEDNESS, AND LIFE CYCLES (Journal of Teleological Science, 2026)
The objective of this work is to investigate the teleological problem represented by economic rationality, addressing three fundamental issues: (i) utility maximization that equates economic rationality with profit-seeking; (ii) the realization of ends through incremental rationality mechanisms; and (iii) the dependence of bounded rationality on life cycles. While these three issues are not the only ones that could be addressed, they should be considered relevant for a better understanding of the relationship between teleological rationality and economics.